Pengaruh Faktor Perilaku 3M Plus dengan Kejadian Demam Berdarah Dengue di Indonesia: A Meta Analysis - Achmad Risyaf Alfalakh (Universitas Airlangga, 2023)
Background: Dengue virus from DHF mosquitoes, until now there is no very good drug or vaccine to prevent and treat DHF, the activities that have been carried out so far have been to improve programs to prevent increase in mortality and vector control. Indonesia generally conducts eradication of mosquito nests which is main activity of preventing dengue cases. This activity requires community intervention. 3M Plus is an effective activity which is carried out by the community by controlling environment, biologically and chemically. Objective: To apply a meta-analysis method for several journals regarding behavioral factors of 3M plus on incidence of dengue hemorrhagic fever in Indonesia and compare the results of the summary effect using Maximum Likelihood and DerSimonian-Laird methods. Methods: Using unobtrusive research with a meta-analysis method to find the difference in estimated maximum likelihood and dersimonian-laird values